Assessing the Impact of Electrode Structure on the Fast Charge Performance of Lithium-ion Batteries. Issue 1 (1st January 2023) - Patel, Prehit; Zhang, Guangsheng; Nelson, George J.
Abstract : Increasing electrode thickness can increase the energy density of lithium-ion batteries. However, increasing electrode thickness increases transport limitations and the risk of lithium plating. This work analyzes prospective improvements to the conventional lithium-ion cell that may facilitate high energy density and fast charging capabilities. A 2D lithium-ion battery model is applied to understand the impact of thick electrode at different C-rates in a single cell stack. Five different cell geometries were analyzed for this work: one conventional cell and four test cases in which the conventional electrode geometries were modified by adding electrolyte channels to increase the rate transfer capability of lithium ions at high C-rates and reduce the risk of lithium plating. All five configurations were simulated in discharge at C/10, C/2, and 1 C followed by simulated charging at 1 C, 3 C, and 5 C with no rest period prior to charge. The addition of electrolyte channels in the anode only results in improved performance with respect to reduced plating risk. Dimensionless parameter analysis was performed to compare the battery performance with different electrode modifications at different C-rates. Scaling behavior based on these parameters clarifies the benefits and limitations of the varied electrode modification approaches.